Book Review: Melacak Jejak Telinga Panjang: Antropologi Fotografi - Niko, Nikodemus (Journal of Society Bridge, 2024)
The book Melacak Jejak Telinga Panjang: Antropologi Fotografi by Ati Bachtiar combines anthropological approaches and photographic art to explore the visual representation of Dayak women. Through the lens of ethnographic photography, this book delves into the cultural significance and identity associated with a nearly vanished cultural practice. The visual analysis demonstrates how photography can serve as a crucial tool in documenting social transformations while preserving cultural heritage. This work offers a fresh contribution to the discourse of visual anthropology by presenting a critical perspective on the relationship between the body, tradition, and photographic documentation.